Volatile Aromatic Compounds (BTEX) in Sediments Offshore Zonguldak Industrial Region, Black Sea, Turkey - Alpar, Bedri; Unlu, Selma (Asian Journal of Chemistry, 2010)
The coastal area off the Zonguldak Industry Region is one of the most-polluted "hot spots" in the anoxic water basin of Black Sea, which is ranked under great anthropogenic pressure among the most ecologically threatened water bodies of the world. Quantitative analyses of volatile aromatic compounds using Finnigan Thermo trace DSQ gas chromato-graphy/mass spectrometry (GC/MS) indicated considerable levels of BTEX (benzene, toluene, ethylbenzene and the mixture of o-, m- and p-xylenes) contamination in the sediment close to many well-identified pollution sources on land. BTEX contamination of seabed sediment was due mostly to benzene except a station off the Zonguldak sea port where xylene was dominant with toluene. The varying concentrations of the contamination throughout the region indicate sea port activities, industrial inputs and partly maritime petroleum transport as the main sources of pollutants.